(untitled) - Clark, Robert H. (New York, 2007)
The focus of this text is the feasibility study. Power engineers gain both the knowledge and the skills needed to accurately determine the feasibility of a proposed tidal power development plan, including: Major factors to consider in selecting a site for preliminary assessment; Tidal power schemes and mode; Hydraulic and mathematical models of estuaries to predict the estuary's response to physical changes and the effects caused by operation of the proposed plant; Civil works required for tidal power development and the associated tidal generating equipment; Procedures to optimize plant output; Economic evaluation and risk assessment; Environmental impact of proposed construction and operation.
Keywords: Water-power,Tidal power,Tidal power-plants